The impact of the kingpin strategy on extortion and kidnapping - Estévez-Soto, Patricio (Criminology & criminal justice, 2025)
The ‘kingpin’ strategy focuses on dismantling criminal groups by apprehending their leaders. However, existing evidence indicates that removing a criminal leader may lead to a surge in organised crime-related homicides, and to spatial displacement of organised crime violence. This study explores the strategy’s impact on other organised crimes, specifically extortion and kidnapping. Analysing Mexican data from 2011 to 2015, we employ a novel matching method for cross-sectional time-series data to assess how leadership removals affect the incidence of extortion and kidnapping, and whether there are any displacement effects. Our results reveal a significant rise in extortions within 6 months of a leadership removal in a municipality, while kidnappings show no significant change. Notably, no spatial displacement effects were observed in neighbouring municipalities post-removal. These findings underscore the unintended consequences of the kingpin strategy, emphasising the need for alternative policies to address organised crime-related violence.